2016
DOI: 10.1021/acs.jpcb.6b09638
|View full text |Cite
|
Sign up to set email alerts
|

Energetic and Dynamic Analysis of Transport of Na+ and K+ through a Cyclic Peptide Nanotube in Water and in Lipid Bilayers

Abstract: Potential of mean force (PMF) profiles and position-dependent diffusion coefficients of Na and K are calculated to elucidate the translocation of ions through a cyclic peptide nanotube, composed of 8 × cyclo[-(d-Leu-Trp)-] rings, in water and in hydrated DMPC bilayers. The PMF profiles and PMF decomposition analysis for the monovalent cations show that favorable interactions of the cations with the CPN as well as the lipid bilayer and dehydration free energy penalties are two major competing factors which dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 60 publications
(127 reference statements)
1
16
0
Order By: Relevance
“…It should be noted that this approach allows us to estimate D ( z ) from techniques using a time-dependent bias, e.g., the adaptive biasing force formalism and metadynamics, as well as from unbiased simulations. For the theoretical foundation and the procedure of computing D ( z ), we refer the reader to Comer et al Previous studies have shown that the choice of the sampling time interval Δ t of CV z in the BI/MC method affects the estimation of D ( z ). , Thus, we have set Δ t equal to 4 ps for all nine models studied here assuming that a constant value will lead to similar uncertainties in all cases. This approximation should be fine in the present case as the idea is to estimate semiquantitative permeation times rather than quantitatively accurate ones.…”
Section: Materials and Methodsmentioning
confidence: 99%
“…It should be noted that this approach allows us to estimate D ( z ) from techniques using a time-dependent bias, e.g., the adaptive biasing force formalism and metadynamics, as well as from unbiased simulations. For the theoretical foundation and the procedure of computing D ( z ), we refer the reader to Comer et al Previous studies have shown that the choice of the sampling time interval Δ t of CV z in the BI/MC method affects the estimation of D ( z ). , Thus, we have set Δ t equal to 4 ps for all nine models studied here assuming that a constant value will lead to similar uncertainties in all cases. This approximation should be fine in the present case as the idea is to estimate semiquantitative permeation times rather than quantitatively accurate ones.…”
Section: Materials and Methodsmentioning
confidence: 99%
“…As a result, depending on the SLE2S monomer position, the simulation time for a single US trajectory in each window varied from 30 to 80 ns, during which the first 10–60 ns and last 20 ns were used as equilibration and production runs, respectively. Two PMF profiles were generated for system 4; one at 1 bar and 350.15 K and the other at 1 bar and 313.15 K. The PMF profile generated for system 5 was calculated at 1 bar and 350.15 K, while the one generated for system 6 was obtained at 1 bar and 313.15 K. Thermodynamic integration (TI) was also employed to decompose the PMF profiles into individual components to determine the influence of each system component on the Gibbs free energy of SLE2S monomer transfer. …”
Section: Computational and Experimental Methodsmentioning
confidence: 99%
“…We chose R c ¼ 10Å because previous MD simulation studies revealed that the diffusion coefficients of ions begin to decrease nearly 10 Å away from the channel entrance of cyclic peptide nanotubes (CPNs) that possess a similar structure to the model nanopore in this study. 29,30 Then, the ion current for ion i can be evaluated as…”
Section: Implementation Of Position-dependent Diffusion Coefficients ...mentioning
confidence: 99%
“…21,[34][35][36][37] Ion-related parameters such as the LJ parameters and diffusion coefficients in bulk water and inside the nanopore are presented in Table 1 where the values of D chn i are set to be 0.4 D blk i for K + , Na + , and Cl À on a basis of the molecular dynamics (MD) simulation results for the position-dependent diffusion coefficients of ions inside a cyclic peptide nanotube (CPN). 29,30 We used the ion radii from the Chemistry at Harvard Macromolecular Mechanics (CHARMM) force field instead of the hydrodynamic radii of ions because our previous MD simulations showed that the ions are partially dehydrated inside a small nanopore like the model system we used in this study. 10,42 A two-dimensional contour map and a one-dimensional profile for the relative position-dependent diffusion coefficient of ion i used in our simulations are illustrated in Figure 2.…”
Section: Implementation Of Position-dependent Diffusion Coefficients ...mentioning
confidence: 99%
See 1 more Smart Citation